Application of SERVQUAL Instrument Dimensions in Nepalese Perspective: A Systematic Review (Prithvi Academic Journal, 2025)
The main purpose of this study was to evaluate the application of service quality instrument dimensions in Nepalese perspective by conducting the systematic review of literature through identifying the major construct variables in the measurement of service quality in different sectors. Therefore, the updated Preferred Reporting Item for Systematic and Meta Analysis (PRISMA) guidelines was followed for systematic review relating to application of service quality instrument dimensions. This systematic review has covered all the article recorded in the NepJOL including website and citation search. The eligibility and inclusion of the article is recorded in the data base of NepJOL dated January 1, 2019 to June 9, 2024, to be written in English, especially, open access, empirical research relating to the topic of service quality. The initial trial and error approach was followed to select the sample articles in NepJOL along with the website and citation search. The study revealed that responsiveness and reliability are more frequently applied dimensions of service quality followed by assurance, empathy and tangibility where others are contextualized including it. The quantitative approach is popular method of measuring the impact of service quality on customer satisfaction and loyalty. This study can provide valuable insight to the business manager, academician, future researcher and policy maker to identify most valuable dimension of service quality useful for the success of business arena and fostering the future direction of such research.